PENGARUH GOOD CORPORATE GOVERNANCE DAN STRATEGI BERSAING TERHADAP KINERJA KEBERLANJUTAN PERBANKAN - Dika Retno Safitri; Theresia Dwi Astuti (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
Global economic conditions that are full of uncertainty mean that companies must have good governance and business strategies in order to survive. This is also an important issue for the banking world. Banking is a business that prioritizes public service and trust. But the case of the bank scandal that broke out resulted in public distrust of the credibility of banks. Bank credibilty greatly affects the sustainabilty of banking. The population used is banking company listed on the Indonesia Stock Exchange year 2015-2019 with a total sample of 200 samples. This study uses multiple linear regression analysis. The purpose of this study is testing the bank credibility by analyzing the influence of good corporate governance and competitive strategy on sustainability performance using a balanced scorecard consisting of financial performance, customer performance, internal business process performance, learning and growth performance, social and environmental performance. The difference in this study compared to previous studies is to use a balanced scorecard to assess the sustainability of banking by adding social and environmental aspects. The result of this study are GCG has a positive effect on financial performance, internal business process performance, growth and learning performance. GCG has no positive effect on customer performance, social and environmental performance. Differentiation has a positive effect on financial performance, internal business process performance, growth and learning performance, social and environmental performance. Differentiation does not affect customer performance.